HIDDEN CURRICULUM SEKOLAH DALAM MENANGKAL RASISME KEBERAGAMAAN - Muhammad Hifdil Islam (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
There is an educational process that is hidden in the curriculum at school, in addition to the process that is raised in the form of teaching and learning activities. The hidden curriculum is an important factor in instilling the character of diversity, especially in countering radicalism. The purpose of this article is to reveal that the hidden curriculum in schools can improve learning outcomes, improve spirituality, and increase students' emotional intelligence. This article is written on the basis of library research, so that the data taken and analyzed is based on the results of thought. Hidden curriculum can improve learning outcomes, improve spirituality, and increase the emotional intelligence of students. Therefore, the hidden curriculum also provides benefits for teachers in providing examples of good behavior to students. The character of a teacher affects students both in the learning process and outside the classroom.